Feasibility, Adherence and Efficacy of Liraglutide Treatment in a Sample of Individuals With Mood Disorders and Obesity - Cuomo, Alessandro; Bolognesi, Simone; Goracci, Arianna; Ciuoli, Cristina; Beccarini Crescenzi, Bruno; Maina, Giuseppe; Rosso, Gianluca; Facchi, Edvige; Maccora, Carla; Giordano, Nicola; Verdino, Valeria; Fagiolini, Andrea (Frontiers in Psychiatry, 2019)
Background Liraglutide is a once-daily injectable medication approved for the treatment of obesity. Hereby we report the feasibly, adherence and efficacy of liraglutide treatment in a sample of individuals with mood disorders and obesity. Methods and Sample Twenty-nine patients with Bipolar or Major Depressive Disorder received liraglutide once daily subcutaneously at a dose gradually titrated from 0.6 mg to 3 mg. All patients were obese and had previously failed multiple healthy lifestyle interventions, including exercise and diet programs. Patients’ weight was recorded before liraglutide treatment (T0) and then 1 (T1), 3 (T3), and 6 months (T6) following T0. Results Mean baseline (T0) weight was 110.54 Kg (± 24.95). Compared to baseline, the percentage of weight loss was 3.37 % at T1, 7.85% at T3 and 10.20% at T6. Thirty-one percent (n = 9) of patients had no side effects, 34.48% (n = 10) had one, 24.14% (n = 7) had two, and 10.34% (n=3) had three side effects. All 29 subjects were still on liraglutide at T1; 79.31% and 48.28% were on liraglutide at T3 and T6. No significant relationship was found between liraglutide dose and likelihood to continue the medication. No patient showed a worsening of the psychiatric condition due to liraglutide treatment. Acceptability and satisfaction with treatment were good for the 48% that completed the study. Conclusions Liraglutide treatment was efficacious, accepted and tolerated by approximately 50% of our sample, followed up for a period of 180 days. Larger, longer, controlled, prospective studies are warranted.